COMPARISON OF THE LEVEL OF INDEPENDENCE IN ADLS IN ELDERLY INSTITUTIONALIZED AND NON-INSTITUTIONALIZED. (Fiep Bulletin - online, 2011)
Introduction: It is known that aging is a natural process of life that brings a series of morphological, functional, biochemical and psychological changes. Although senility isn't synonymous of disease, many elderly have functional disabilities may lead to total dependence. Objective: The research aims to compare the level of independence to perform of activities of daily living (ADL's) in elderly residents of those institutions and non-institutionalized. Methodology: The epidemiological study is the type of cross-sectional comparative data with a probability sample. The sample consisted of 30 elderly, between 70 and 80 years living in nursing home and participants of action and citizenship project of Assis Gurgacz College. Being aplied the Barthel index questionnaire, with modified scale, with 15 closed questions that ponctuated the level of independence of the elderly. The data were tabulated and analyzed by Microsoft Excel 2007 program. Results: In the analysis of the total score was found a considerable difference between the two groups, and the institutionalizes elderly had a lower score than the non-institutionalized. However the level of personal autonomy, even showing differences, these were minimal, since in both groups an average of six people who have achieved the maximum score. We found the disparity in the level of mobility where the elderly resident in nursing home had about half the score when compared to another group. Conclusion: We conclude that there is considerable difference of independence between groups. Since the institutionalized did not physical exercise which lead to a greater deficit in the mobility level, while non-institutionalized have better mobility.
Keywords: Elderly; Level of independence; Activities of daily living